Effect and mechanism of GLP-1 on cognitive function in diabetes mellitus - Dou, Xiaoke; Zhao, Lei; Li, Jing; Jiang, Yaqiu (Frontiers in Neuroscience, 2025)
BackgroundDiabetes mellitus (DM) is a metabolic disorder associated with cognitive impairment. Glucagon-like peptide-1 (GLP-1) and its receptor (GLP-1R) have shown neuroprotective effects.Scope of reviewThis review explores the impact of DM on cognitive function. Diabetes-related cognitive impairment is divided into three stages: diabetes-associated cognitive decrements, mild cognitive impairment (MCI), and dementia. GLP-1R agonists (GLP-1RAs) have many functions, such as neuroprotection, inhibiting infection, and metabolic regulation, and show good application prospects in improving cognitive function. The mechanisms of GLP-1RAs neuroprotection may be interconnected, warranting further investigation. Understanding these mechanisms could lead to targeted treatments for diabetes-related cognitive dysfunction.Major conclusionsTherefore, this paper reviewed the regulatory effects of GLP-1 on cognitive dysfunction and its possible mechanism. Further research is required to fully explore the potential of GLP-1 and its analogs in this context.